Ethylene signaling: simple ligand, complex regulation - Merchante-Berg, Catharina; Alonso, José M.; Stepanova, Anna (ELSEVIER, 2013)
The hormone ethylene plays numerous roles in plant development. In the last few years the model of ethylene signaling has evolved from an initially largely linear route to a much more complex pathway with multiple feedback loops. Identification of key transcriptional and post-transcriptional regulatory modules controlling expression and/or stability of the core pathway components revealed that ethylene perception and signaling are tightly regulated at multiple levels. This review describes the most current outlook on ethylene signal transduction and emphasizes the latest discoveries in the ethylene field that shed light on the mechanistic mode of action of the central pathway components CTR1 and EIN2, as well as on the post-transcriptional regulatory steps that modulate the signaling flow through the pathway.
Keywords: Hormonas vegetales; Ethylene; Signal Transduction; Plants; Arabidopsis; Phitohormone